New Zealand personnel consultants and the selection process : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - Harris, Natalie Joy (Massey University, 1992)
A survey of New Zealand personnel consultants was conducted which focused on the managerial selection process. Overall, the results were found to be similar to other New Zealand and overseas studies for the use and perceived validity of selection methods. Personnel consultants do not appear to have an accurate perception of the validity of most selection methods. They also frequently use those selection methods which are not particularly valid. The correlation between the reported validity of the 27 selection methods included and the perceived validity of these selection methods was small (Spearman's rho = 0.319). As was expected, the respondents' perception of the validity of the managerial selection methods included in the questionnaire had a stronger relationship with their use of those selection methods (rho = 0.622, p < .01). However, when one looks at the individual Pearson product moment correlations for each individual selection method, only half were significant. The correlation between use and reported validity was only slight. Surprisingly it was also negative (rho = -0.220). A disturbing result was found when calculating this relationship using only the most frequently used selection methods. The correlation was again negative, however, it was a lot stronger, rho = -0.62 (p < .05). This means that for the most frequently used selection methods the higher the reported validity of a selection method the less often personnel consultants used it and the lower the level of validity the more frequently personnel consultants used it.
Keywords: Personnel management; Executive recruitment; Business consultants; Personnel consultants; Managerial selection